Radiological protection and safety: Putting patients first - Reddy Ravikanth (Wolters Kluwer Medknow Publications, 2019)
The concept of radiation safety has always been a hot topic, especially with the late reports pointing to increased hazards with chronic radiation exposure for patients and medical personnel alike. Appropriate use of equipment include collimation, optimizing beam-on time, minimizing distances between image intensifier and patient, ensuring sufficient distance between patient and x-ray tube, and optimizing exposure rates for image quality and dose. Present day diagnostic radiology relies on three radiation protection principles - Justification of practice safety, optimization of radiation exposure ALARA, and dose limitation. General practitioners need a working knowledge of radiation safety as to adequately inform their patients of the risks-benefit ratio of diagnostic imaging procedures